(untitled) (Agricultural Engineering, 2017)
A single-factor field experiment concerned calculation of fuel consumption, time expenditure of the working time of machines, and winter wheat yield size in three technologies of soil cultivation. Fuel consumption in the tillage and non-tillage technology was comparable and amounted approximately to 31 l·ha−1, but the highest consumption was generated by basic soil cultivation (tillage or heavy cultivation cultivator). Fuel consumption in the strip cultivation technology was the lowest and it was 23.0 l·ha−1. Non-tillage cultivation allowed reduction of the time necessary to carry out the wheat cultivation technology by 28.8% (in comparison to tillage cultivation). On the other hand, strip cultivation allowed reduction of the total time of machines operation by 48.5 % (in comparison to tillage cultivation). The yield of winter wheat cultivated in the non-tillage technology was at the average by 4% better than the one cultivated in tillage cultivation. The highest yield of seed (7.63 t·ha−1) was obtained in the strip cultivation technology (by 6.7% in comparison to tillage cultivation).